KAJIAN AKTIVITAS ANTIOKSIDAN ALGA COKLAT Padina australis DARI PERAIRAN PANTAI SUNDAK GUNUNG KIDUL - Maini, Mela; Ibrahim, Ratna; Rianingsih, Laras (Jurnal Pengolahan dan Bioteknologi Hasil Perikanan, 2013)
One of brown algae species that contains bioactive compounds was P. australis.Several studies on the antioxidant activity of brown algae including P. australis from JavaNorthern waters have already done above temperature 500C which was mostly resulted in lowantioxidant activity. This study aimed to know the polarity properties of bioactivecompounds, the compounds that act as antioxidants, the effect of three solvent types which isdifferent polarity on antioxidant activity, the total phenolic, the chlorophyll and carotenoidscontents as well as their correlation to the percentage of free radicals inhibition. Materialsused in this study were fresh P. australis which obtained from Sundak coastal waters. Thereasearch method applied was experimental laboratories. The experimental design used wasÂ Block Randomized Design with three treatments of solvents types which has differentpolarity, namely n-hexane, ethyl acetate and ethanol. Each of the treatments was done intriplicate. The main variable measured was antioxidant activity. The other variablesmeasured were the total phenolic, the chlorophylls and carotenoids contents. The data wereanalyzed by ANOVA and tested with an Honestly Significant Different test. The resultsshowed that the characteristic of bioactive compounds that act as antioxidants in the P.australis was semipolar. The lowest IC50 value was 282,967 ppm which categorized in lowcategory of antioxidant activity. Maceration of the sample using three solvent types which isdifferent polarity caused the antioxidant activity values of the P. australis extract differsignificantly. The highest total phenolic, chlorophyll a, chlorophyll b and carotenoid contentsobtained from the sample extracted by ethyl acetate solution was 59.41 mg GAE / g sample,2.674 mg / g sample, 2.235 mg / g sample and 2.256 mg / g sample respectively. Each of thevalues was positively correlated with the percentage of free radical inhibition.